# Problem 24 from Chapter 1 of Kunen's Set Theory: An Introduction to Independence Proofs

Just want to make sure I'm tracking Kunen here, and hopefully the proof I have is correct. Comments / Suggestions welcome.

Thanks!

Problem 24. Let T be any consistent set of axioms extending ZF. Show that the Z = {$\psi$ : T $\vdash \psi$} is not recursive.

Proof:

We prove the contrapositive. So suppose Z recursive. Then

i. There is a $\chi(x)$ s.t. T $\vdash \psi$ $\implies$ ZF $\vdash \chi$(' $\psi$ ')

ii. There is a $\chi(x)$ s.t. T $\nvdash \psi$ $\implies$ ZF $\vdash \lnot \chi$('$\psi$')

for any $\psi$. We note:

14.2: ZF $\vdash \psi \iff \lnot \chi$('$\psi$').

We must show T inconsistent (i.e., T $\vdash \bot$).

Subproof 1.

Suppose T $\vdash \psi$.

ZF $\vdash \chi$('$\psi$') -- By i. and assumption

T $\vdash \psi \iff \lnot \chi$('$\psi$') -- 14.2 + the fact that T is an extension of ZF

T $\vdash \chi$ ('$\psi$') -- Again, T is an extension of ZF

T $\vdash \chi$('$\psi$') $\iff \lnot \chi$('$\psi$').

Hence T $\vdash \bot$ .

End of Subproof 1.

Subproof 2.

Suppose on the other hand T $\nvdash \psi$.

ZF $\vdash \lnot \chi$('$\psi$') -- By assumption and ii.

ZF $\vdash \psi$ -- Previous line and 14.2.

T $\vdash \psi$ -- T is an extension of ZF

T $\vdash \psi \iff$ T $\nvdash \psi$

T $\vdash \bot$.

End of Subproof 2.

Hence either way, T $\vdash \bot$.

End of Proof.

• Actually, I just thought of a question related to this. Maybe someone who knows better than me can correct me if I'm wrong, but from this theorem doesn't it follow that ZF is essentially undecidable, and therefore incomplete? There might be stronger notions of incompleteness I'm not aware of that might apply as well. Jan 28 '14 at 4:18
• For the deducibility relation, you can use the "\vdash" latex symbol, in order to get : $\vdash$. Jan 28 '14 at 7:27
• Wonderful, really appreciate the advice with formatting. But is the proof correct? (I suspect it is) Jan 28 '14 at 15:18
• I have not studied Kunen's book, so I prefer to give the "burden of proof" to someone more expert than me. The passages "looks good"; what I'm not able to "assess" is $14.2$, that has a crucial role in your proof (but I think is a result already proved by Kunen). Jan 28 '14 at 15:26
• 14.2 is most certainly a consequence of what is proven by Kunen (page 40), which is the "diagonal lemma." The lemma itself looks like ZF $\vdash$ $\psi$ $\iff$ $\phi$('$\psi$'), where $\phi$(x)is any formula in one free variable. Jan 28 '14 at 15:48

No, your proof is not correct.

Here is my attempt:

Theorem

(Assume ZF is consistent.) Let $T$ be any consistent set of axioms extending $\mathrm{ZF}$.

Then $\{ \psi : T \vdash \psi \}$ is not recursive.

Proof. Assume it were recursive. We show that $T$ is inconsistent. By Theorem 14.1, we find a formula $\chi(x)$ such that

• $T \vdash \psi$ implies $\mathrm{ZF} \vdash \chi(\ulcorner \psi \urcorner)$ and
• $T \nvdash \psi$ implies $\mathrm{ZF} \vdash \neg \chi(\ulcorner \psi \urcorner)$.

By Theorem 14.2 (the fix-point lemma), we find a sentence $\psi$ such that $\mathrm{ZF} \vdash (\psi \leftrightarrow \neg \chi(\ulcorner \psi \urcorner))$.

We assume $T \nvdash \psi$. Then $\mathrm{ZF} \vdash \neg \chi(\ulcorner \psi \urcorner)$ and thus $\mathrm{ZF} \vdash \psi$ contradicting $T \nvdash \psi$.

So $T \vdash \psi$. Then $\mathrm{ZF} \vdash \chi(\ulcorner \psi \urcorner)$, so $\mathrm{ZF} \vdash \neg \psi$, whence $T \vdash \neg \psi$. So $T \vdash (\psi \land \neg \psi)$, i.e. $T$ is inconsistent.

QED.

Note that this theorem (like all theorems in section I.14) are facts proven in the metatheory. Do not confuse formal theorems like

$$\forall a, b, c, d \ \Bigl( \langle a, b \rangle = \langle c, d \rangle \leftrightarrow (a = c \land b = d) \Bigr)$$

and facts in the metatheory like

$$\mathrm{ZF} \vdash \forall a, b, c, d \ \Bigl( \langle a, b \rangle = \langle c, d \rangle \leftrightarrow (a = c \land b = d) \Bigr).$$

We prove the contrapositive. So suppose $T$ recursive. Then

i. There is a $\chi(x)$ s.t. $T \vdash \psi \implies \mathrm{ZF} \vdash \chi(\ulcorner \psi \urcorner)$.

ii. There is a $\chi(x)$ s.t. $T \nvdash \psi \implies \mathrm{ZF} \vdash \neg \chi(\ulcorner \psi \urcorner)$.

for any $\psi$.

First of all, do not mix the metatheory and the theory: You use "$\implies$" at both levels! Also, there is just one $\chi(x)$ such that

• $T \vdash \psi$ implies $\mathrm{ZF} \vdash \chi(\ulcorner \psi \urcorner)$ and
• $T \nvdash \psi$ implies $\mathrm{ZF} \vdash \neg \chi(\ulcorner \psi \urcorner)$.

You stated the existence of two (maybe different) formulas.

We note:

14.2: $\mathrm{ZF} \vdash \psi \iff \neg \chi(\ulcorner \psi \urcorner)$.

There is some $\psi$ such that $\mathrm{ZF} \vdash (\psi \leftrightarrow \neg \chi(\ulcorner \psi \urcorner))$.

We must show $T$ inconsistent (i.e. $T \vdash \bot$).

Subproof 1.

What is a "subproof"? The structure of your proof is wrong at this point. A case differentiation does not make sense here because $T \nvdash \psi$ leads to a contradiction. So $T \vdash \psi$ anyway!

Suppose $T \vdash \psi$.

$\mathrm{ZF} \vdash \chi(\ulcorner \psi \urcorner) \quad$ -- By i. and assumption

$T \vdash \psi \iff \neg \chi(\ulcorner \psi \urcorner) \quad$ -- 14.2 + the fact that $T$ is an extension of $\mathrm{ZF}$

$T \vdash \chi(\ulcorner \psi \urcorner) \quad$ -- Again, $T$ is an extension of $\mathrm{ZF}$

$T \vdash \chi(\ulcorner \psi \urcorner) \iff \neg \chi(\ulcorner \psi \urcorner)$

Why "$\iff$"? It must be $T \vdash (\chi(\ulcorner \psi \urcorner) \land \neg \chi(\ulcorner \psi \urcorner))$.

Hence $T \vdash \bot$.

End of Subproof 1.

Subproof 2.

Suppose on the other hand $T \nvdash \psi$.

Your (main) claim is that $T$ is inconsistent. Then $T \nvdash \psi$ cannot be true (because an inconsistent theory proves everything), so you have to treat this as an assumption and not as a second case. You must derive a contradiction, i.e. a contradiction in the metatheoretical logic of your proof. This is not the same as an inner-theoretical contradiction in $T$.

$\mathrm{ZF} \vdash \neg \chi(\ulcorner \psi \urcorner) \quad$ -- By assumption and ii.

$\mathrm{ZF} \vdash \psi \quad$ -- Previous line and 14.2.

$T \vdash \psi \quad$ -- $T$ is an extension of $\mathrm{ZF}$.

$T \vdash \psi \iff T \nvdash \psi$

Why "$\iff$"? It must be $T \vdash \psi$ and $T \nvdash \psi$.

This step is a big mistake! Be careful with your use of "$\iff$". You seem to confuse the metatheory and the theory.

$T \vdash \bot$

$T \vdash \psi$ and $T \nvdash \psi$ is the (metatheoretical) contradiction. $T \vdash \bot$ does not make any sense as you assumed $T \nvdash \psi$ (see above).

End of Subproof 2.

Hence either way, $T \vdash \bot$.

End of Proof.

• You've said my proof is incorrect, but you haven't said why. Could you be a little more specific? Apr 3 '14 at 20:58
• Fair enough. I added an analysis of your proof to my answer. Apr 4 '14 at 11:44